A Dynamic Capability View on Tourism Supply Chain Resilience: Evidence from Indian Tourism Sector - ROY, Souvik; AMAR, Raju G.; MANDAL, Santanu (Journal of Environmental Management and Tourism; Vol 7 No 1 (2016): JEMT Volume VII, Issue 1(13) Spring 2016, 2016)
Tourism supply chains need to be resilient so as to restore operations from increasing disruptions. Hence we argue in this empirical examination using dynamic capability view that firms in tourism supply chains will use their variable, renewable, inimitable and non-substitutable (VRIN) resources and non VRIN resources to develop tourism supply chain resilience to recover from disruptions in a swift manner. Further, we posit such tourism supply chain resilience as a dynamic capability that will impart positive supply chain performance for partnering firms. Empirical findings obtained as a result of 233 complete responses and analyzed using PLS suggests VRIN and non-VRIN resources to as significant enablers of tourism supply chain resilience and such a capability result in a positive tourism supply chain performance. Further, our study revealed perceived environmental dynamism as a dominant moderator influencing the proposed linkages among VRIN; non-VRIN resources and tourism supply chain resilience.
Keywords: tourism supply chain; resilience; environmental dynamism; VRIN resources; supply chain performance